From Theological Loyalty to Humanistic Integrity: A Maqāṣidī Reconstruction of the Qur’anic Verses on Al-Walā’ wa Al-Barā’ - Fathurrosyid; Achmad Lutfi; Mustofa As’ady; Mahmudi (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
This article reconstructs the theological concept of Al-Walā’ wa Al-Barā’ through a maqāṣidī interpretive approach within the context of Indonesia’s plural and multicultural society. The study stems from an epistemological problem regarding literal readings of Qur’anic verses on loyalty, which tend to foster identity-based exclusivism and the delegitimization of non-Muslim groups. Unlike previous studies that predominantly examine Al-Walā’ wa Al-Barā’within the frameworks of Salafi-jihadi ideology and identity politics, this article offers a maqāṣidī reinterpretation by integrating textual analysis, socio-historical context, and the universal objectives of Islamic law (maqāṣid al-sharī‘ah). Employing a qualitative library-based method focusing on Q. 5:57, Q. 9:23, and Q. 60:1, the study demonstrates that the prohibition of loyalty in these verses is not inherently based on non-Muslim identity, but rather on acts of religious mockery, active hostility, political betrayal, and security threats to the Muslim community. Consequently, the effective cause (‘illah) of the prohibition is ethical and contextual rather than theological-discriminatory. The study further argues that Al-Walā’ should be reinterpreted as a commitment to justice, communal protection, and public welfare, while Al-Barā’ signifies the rejection of destructive actions that threaten social peace. Through this approach, the paradigm shifts from identity-based theological loyalty toward humanistic integrity and civic loyalty compatible with religious pluralism, democracy, and Indonesia’s constitutional principles. This study contributes to the development of contemporary maqāṣidī exegesis, particularly in reinterpreting Qur’anic verses on religious loyalty within multicultural societies.